TAHAYUL SEBAGAI PENDIDIKAN KARAKTER ANAK: KAJIAN ETNOPEDAGOGIEK - I Nyoman Daging; I Nengah Adi Widana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Growing children's character needs to be done from an early age with various efforts made by parents to their children. There are many ways to do it, starting with the easiest one, which is to scare with various superstitions. In this era of globalization, there are still many people educating children's character with superstition because they have the belief that the child's character will be good, some people have left superstition as an alternative to educating children because they think it is outdated. The superstition that develops in Bali generally begins with the phrase sing dadi, which is then apang tusing this implies an element of cause and effect. As for some examples of character education developed with this superstition are religious character, character of discipline, character of responsibility, and character of manners.Keywords: Superstition, Character Education, Ethnopedagogiek